Bioremediation of dyes: Current status and prospects. (December 2020) - Ihsanullah, Ihsanullah; Jamal, Arshad; Ilyas, Muhammad; Zubair, Mukarram; Khan, Gulraiz; Atieh, Muataz Ali
Graphical abstract: Highlights: A comprehensive overview of bioremediation in water treatment is presented. The potential of microorganisms for the uptake of dyes are portrayed in detail. Recent advancements in the bioreactors and microbial fuel cells are emphasized. The major challenges in the bioremediation applications are accentuated. A roadmap for future research is suggested. Abstract: Environmental pollution associated with the discharge of textile industries is becoming a global concern. There is an imperative need for developing efficient, environmentally friendly, and cost-effective techniques for treating the wastewater containing dyes. Bioremediation of dyes is a fascinating approach to treat the textile effluents as it offers many advantages over the conventional treatment techniques. This review critically evaluates the latest advancements in applications of bioremediation techniques for the removal of various dyes from wastewater. The applications of various microorganisms such as bacteria, algae, fungi, yeast, and enzymes for the uptake of dyes are portrayed in detail. The current advancements in the bioremediation of textile effluents, research opportunities, challenges, and future outlook are emphasized. It also highlights the progress in bioremediation of dyes using bioreactors and microbial fuel cells. This review is beneficial in understanding the current status of bioremediation in water purification and accelerating the research focusing the role of bioremediation in water purification applications in future.